Anti-washout tricalcium silicate cements modified by konjac glucomannan/calcium formate complex for endodontic applications. Issue 17 (1st September 2022) - Wu, Meng; Tao, Bailong; Wu, Wangping
Abstract: Although tricalcium silicate (TCS)-based cement showed a great clinical success as the dental filling material, a big challenge encountered by TCS is its poor anti-washout property. Thus, the purpose of this study is to develop a novel TCS-based cement with excellent anti-washout ability by incorporation of konjac glucomannan (KGM)/calcium formate (CF) complex. The self-setting characteristics, anti-washout ability, setting time, compressive strength, porosity, injectability and flowability of the cements were investigated. Furthermore, antibacterial property and cell cytocompatibility of TCS/CF were also assessed. The results showed that KGM could enhance the washout resistance of TCS pastes while it hindered hydration reaction. CF can further increase the anti-washout ability of TCS cement and shorten its setting time from 420 to 174 min because of the accelerating effect of CF on hydration kinetics of TCS. Compared with TCS pastes, TCS cement containing CF showed an increased compressive strength while the addition of CF decreased the injectability of pastes without an obvious effect on flowability. The antibacterial activity of TCS/CF against S. aureus increased with the amount of CF. Moreover, TCS/CF had good cell cytocompatibility. Our results suggested that incorporation of KGM/CF is a superior strategy to enhance the anti-washout ability of TCS-based dental cements, which have the potential use for endodontic applications.